Postpartum Depression: Epidemiological Clinical Profile of Patients Attended In a Reference Public Maternity in Salvador-BA - Ivan de Sousa Araújo; Karolina Sales Aquino; Luciana Kelly Amado Fagundes; Vanessa Cruz Santos (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2019)
Abstract Objective To evaluate the clinical epidemiological state of women with suspected post partum depression (PPD) in a public maternity hospital in Salvador, state of Bahia, Brazil. Methods A cross-sectional research was performed with puerperal patients attended at a public maternity hospital in Salvador, Bahia. Data collection was performed from June to September 2017. The Edinburgh Postnatal Depression Scale was used as a screening instrument, and, subsequently, women with positive scores answered a questionnaire to identify their clinical and epidemiological status. Results Out of 151 postpartum women from the research, 30 (19.8%) presented suspicion of PPD. There was a prevalence of single mothers 13 (43.3%), women with complete fundamental education 15 (50.0%), women with black skin color 14 (46.7%), and those with a monthly family income of up to one minimum wage 18 (40.0%). Conclusion Although PPD is an underdiagnosed disease, a high prevalence of the condition was found in our research. It is, then, considered that these results reinforce its significance as a public health problem, requiring prevention strategies, early diagnosis and effective treatment.